ENCOURAGING LITERACY HABITS TOWARDS EARLY CHILDREN AT CIPAYUNG - nurul frijuniarsi; natalia tri astuti (Universitas PGRI Sumatera Barat, 2021)
Establishing literacy habits cannot be obtained in one or two days, it takes a habituation that is repeated and consistent. This habituation can start from the child's first social environment, the family. In addition, the school can provide support by being a mediator or facilitator. Therefore, this PKM was carried out with the aim of encouraging literacy habits at home and school, with PAUD Matahari Cipayung as the partners and students and their parents as targets. The PKM activity was carried out for three months, and the results of the activity showed that most parents had a high awareness of the importance of literacy skills for children, besides that there were also significant changes in the interaction patterns of children and parents which were more communicative and interactive. Overall, it can be concluded that this PKM activity is able to achieve the expected target, the creation of literacy habits in early childhood